BUSINESS STRATEGY FORMULATION OF DAYA MINYAK, Ltd - Anugerah Satiawarman; Tanti Sutandra; Ningky Sasanti Munir (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2021)
The weakening of crude oil price had caused the performance of Daya Minyak, Ltd decline. The efforts to improve had succeeded in improving performance, but it was still below the industry average. Therefore, in 2020 a research was carried out aimed at systematically formulating Daya Minyak, Ltd business strategy for the years 2021-2024. This applied research was conducted qualitatively, using the business strategy formulation model from David and David (2016) where external strategic issues were compiled in the External Factor Evaluation (EFE) matrix and internal strategic issues in the International Factor Evaluation (IFE) matrix. The weighted value of the EFE matrix is 2.93 and the weighted value of the IFE matrix is 2.97, which meant that the future business strategy is to hold and maintain. Two alternative strategies, market penetration, and product development were developed using the Internal-External (IE) matrix and the TOWS matrix. Two priority strategies, namely a strategy to increase market penetration through integrated services at low costs and a product development strategy through increasing local content with international standards are determined by the Quantitative Strategic Planning Matrix (QSPM).